Simultaneous presence of poly titanium chloride and Fe2O3-Mn2O3 nanocomposite in the enhanced coagulation for high rate As(V) removal from contaminated water. (August 2020) - Eslami, Hadi; Esmaeili, Abbas; Ehrampoush, Mohammad Hassan; Ebrahimi, Ali Asghar; Taghavi, Mahmoud; Khosravi, Rasoul
Graphical abstract: Highlights: Enhanced coagulation of As(V) investigated by simultaneous coagulant + nanocomposite. As(V) removal efficiency (>99 %) significantly increased by PTC + Fe2 O3 -Mn2 O3 . The FESEM-EDX analysis confirmed coagulant-nanocomposites combined flocs formation. With 10 % combined flocs recirculation, the coagulant consumption decreased by 25 %. Abstract: High rate Arsenic (As (V)) removal from contaminated water resources was investigated by simultaneous presence of poly titanium chloride (PTC) and Fe2 O3 -Mn2 O3 nanocomposite in the enhanced coagulation process along with precipitated flocs recirculation. In this study, the synthesis of Fe2 O3 -Mn2 O3 and PTC and their characteristics, the effective parameters in the enhanced coagulation process, including pH, coagulants dosage, initial concentrations of As (V), nanocomposite dosage, as well as the rate of precipitated floc recirculation were tested. According to the FTIR analysis, the prepared PTC coagulant contained −OH, Ti−OH, and TiO bonds, confirming coagulant polymerization. The highest As (V) removal efficiency (99.96 %) by PTC + Fe2 O3 -Mn2 O3 occurred at pH 7, coagulant dose of 20 mg/L, and up to 300 μg/LAs (V) initial concentration. Moreover, the residual turbidity was 4NTU and the residual As (V) was less than 0.1 μg/L. However, in absence of nanocomposite, the residual As (V) was 17.1 μg/L in optimal conditions. The FESEM-EDX analysis confirmed coagulant-nanocomposites combined flocs formation and the presence of Fe, Mn and As elements in flocs. The precipitated flocs recirculation had also a significant effect on reducing the coagulant dosage; moreover, with a 10 % combined flocs recirculation, the consumption of PTC coagulant dosage decreased by 25 %. Therefore, the enhanced coagulation process in the presence of Fe2 O3 -Mn2 O3 nanocomposite along with the precipitated flocs recirculation could be introduced as an effective and efficient process in Arsenic removal from contaminated water.